John Smith correspondence - Smith, John, approximately 1735-1824.
ALS (1807 August 13) from Smith to George Gordon and ALS (1808 January 25) from Smith to Nathaniel Evans relating to the Burr conspiracy and other legal matters.
Typewritten transcript of Smith's letter to Evans is also available.
U.S. senator from Ohio, public official of the Northwest Territory, and clergyman.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Evans, Nathaniel -- Correspondence; Gordon, George, -- active 1807 -- Correspondence; Burr Conspiracy, 1805-1807.; Clergy; Public officials -- Northwest Territory; Senators, U.S. Congress -- Ohio